Cholecystitis and hemobilia - Staszak, Jessica K (J Surg Case Rep, 2019)
Hemobilia, or hemorrhage into the biliary system, is an unusual cause of gastrointestinal bleeding most commonly seen in accidental or iatrogenic trauma. We present the rare case of a 43-year-old gentleman who presents with an intrahepatic pseudoaneurysm caused by cholecystitis. The management of the hemobilia was technically challenging requiring multiple interventional procedures. We review the pathophysiology and treatment strategies for this rare case of gastrointestinal hemorrhage.